Effects of pH-neutral, bicarbonate-buffered dialysis fluid on peritoneal transport kinetics in children - Schmitt, Claus P.; Haraldsson, Börje; Doetschmann, Rouven; Zimmering, Mirjam; Greiner, Christine; Böswald, Michael; Klaus, Günter; Passlick-Deetjen, Jutta; Schaefer, Franz (Kidney international, 2002)
Effects of pH-neutral, bicarbonate-buffered dialysis fluid on peritoneal transport kinetics in children. - Background - Due to their superior biocompatibility, pH-neutral solutions are beginning to replace acidic lactate-buffered peritoneal dialysis (PD) fluids. We hypothesized that pH-neutral and acidic solutions might differentially affect peritoneal transport in the early dwell phase, due to differences in ionic shifts and initial peritoneal vasodilation. Such differences may become clinically relevant in patients with frequent short cycles on automated PD (APD).
Available online 16 December 2015
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.01.2021